Psychiatric Disturbances in Patients and Relatives Due to Intensive Care Admission - Winardi, Ignatius Aldo (HM Publisher, 2023)
The issue of psychiatric disorders arising from the admission of inpatient patients and their relatives has persisted for a significant period of time. This phenomenon may occur as a result of psychological trauma experienced by either the patient or their family. The majority of the family members experience fear and anxiety around the potential loss of their loved ones. Recent research has indicated that a significant proportion, ranging from 51% to 69%, of individuals within familial relationships exhibit this particular occurrence. Outpatient cardiac arrest (OCA) is recognized as a highly influential occurrence in precipitating this psychological phenomenon. The management of critically ill patients in the intensive care unit (ICU) presents a complex and demanding task. The individual's status undergoes quick and unpredictable fluctuations. The presence of ambiguity gives rise to the development of delirium, which is characterized as a state of acute brain malfunction and is observed in 50–80% of patients in the intensive care unit (ICU). The phenomenon is also correlated with prolonged hospitalizations and increased mortality rates. This review was aimed to described psychiatric disturbances in patients and relatives due to ICU admission.